2022
DOI: 10.3390/children9111721
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Stimulating Environment Predicts Later Childhood Resilience in an Indian Longitudinal Birth Cohort Study

Abstract: Background: Human resilience is dynamic and generated through myriad interactions starting from early childhood. Resilience can improve quality of life and longevity. Objective: The current analysis evaluates childhood resilience at 9 years of age and its associations with concurrent cognition and early childhood factors, using longitudinal follow-up of a community birth cohort in Vellore, south India. Methods: Resilience was assessed using the Child and Youth Resilience Measure and cognition utilizing the Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This greater focus on environments, especially, is becoming more commonplace in studies of resilience globally. For example, a birth cohort study from South India (Koshy et al, 2022) with 9-year-olds showed that cognitive performance on an intelligence test could be predicted by a range of factors at age two, including biological (growth stunting), family (maternal depression), environmental (quality of stimulation at home), and socioeconomic status. Like other studies from other countries, resilience was associated with a unique and contextually specific constellation of factors, in this instance the quality of the home environment and verbal intelligence, though not the other systemic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This greater focus on environments, especially, is becoming more commonplace in studies of resilience globally. For example, a birth cohort study from South India (Koshy et al, 2022) with 9-year-olds showed that cognitive performance on an intelligence test could be predicted by a range of factors at age two, including biological (growth stunting), family (maternal depression), environmental (quality of stimulation at home), and socioeconomic status. Like other studies from other countries, resilience was associated with a unique and contextually specific constellation of factors, in this instance the quality of the home environment and verbal intelligence, though not the other systemic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Even when one or more systems are found to be non-significant to a hypothesized model, the field of resilience is increasingly moving toward looking at the systems which were not assessed (e.g., in the Koshy et al, [2022] study, one could assume that access to a supportive educational system, exposure to domestic violence, and other stressors and resources may have influenced findings). Indeed, to fully capture the many systemic interactions associated with resilience, evidence is needed from many different studies, each focused on a different set of systems with some overlap.…”
Section: Implications For Resilience Researchmentioning
confidence: 99%
“…Children were divided into four categories based on their stunting status at two, five, and nine years of age: Group NS: children who were never stunted, Group S2N5: children who were stunted at two years with a catch-up at five years, and Group S5N9: children stunted at two and five years, with a catch-up at nine years, and Group AS: children stunted at two, five, and nine years [14]. Details of baseline demographic information and clinical characteristics were summarised.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…251 new-borns were enlisted between March 2010 and February 2012 and followed up at different time points including at ages two, five, and nine years. Details of enrolment and follow-ups are already published [13][14][15]. At each level, enrolment of the child was conditional upon written informed consent from parents, with additional child assent required at the age of nine.…”
Section: Settings and Participantsmentioning
confidence: 99%